Performance Analysis of a Direct Torque Controlled PV Water Pumping System Using Grey Wolf Optimizer and Incremental Conductance Maximum Power Point Tracking under Variable Irradiance - Idbouhouch, Oussama; Zegrari, Mourad; Rabbah, Nabila (Engineering, Technology & Applied Science Research, 2026)
This paper presents a performance analysis of a Photovoltaic (PV) water pumping system driven by an Induction Motor (IM) and controlled through the Direct Torque Control (DTC) strategy. The DTC approach was implemented to directly regulate the electromagnetic torque and stator flux, thereby ensuring fast dynamic response and high-efficiency operation. To optimize the energy conversion process under variable irradiance, two Maximum Power Point Tracking (MPPT) techniques were integrated into the DC–DC boost converter: the Incremental Conductance (INC) and the Grey Wolf Optimizer (GWO). The main objective of this study is to assess and compare the dynamic and steady-state performance of the DTC–INC and DTC–GWO configurations under both uniform and partially shaded conditions. The simulation results, performed using MATLAB/Simulink, show that while both strategies achieve stable operation under normal irradiance, the GWO-based MPPT exhibits superior adaptability under partial shading by accurately locating the Global Maximum Power Point. This results in an approximate 32% increase in hydraulic power relative to the INC approach, thereby improving torque stability, accelerating convergence, and increasing hydraulic efficiency. This study contributes to the advancement of intelligent PV-based pumping systems by integrating heuristic optimization and high-performance motor control, offering a promising solution for sustainable water supply in remote and semi-arid regions.